Comparison of Two Doses of Cisatracurium (0.15mg/Kg and 0.2mg/Kg) in a Single Centre, Prospective, Comparative, Parallel Group of Patients Undergoing General Anesthesia with Endotracheal Intubation by Studying Ease of Intubation - Kiran Chheda; Vyankatesh Munje; Alka Halbe (International Journal of Medical Science and Clinical Research Studies, 2023)
Objective : Study the advantages and pitfalls of both 0.15 mg/kg and 0.2 mg/kg of Cisatracurium for Intubation. Background: The patients coming to a Tertiary Care Hospital during period 2018-2019 for surgery under General Anaesthesia, who met the Inclusion Criteria were studied in a hundred patients. After giving all components of balanced general anaesthesia, patients randomised into 2 groups either 0.15 mg/kg or 0.2mg/kg of Cisatracurium as a muscle relaxant and Intubation was done at 3 minutes. Measurements and Results: Heart rate, Blood pressure, Systolic, Diastolic, Mean, SpO2, ETCO2, TOF monitoring at the adductor pollicis, and BIS were monitored for 7 minutes and Intubating conditions in both the groups were evaluated, and scored according to the Steyn’s Modification of Helbo-Hansen Scoring system. In haemodynamic changes in Group A [0.15 mg/kg] Heart rate and Blood pressure showed an increasing trend before coming down to baseline by 7 minutes. In Group B [0.2mg/kg] the trend was decreasing from baseline after a minor increase in heart rate at 2 minutes and Mean Blood pressure was lower at all intervals when compared to baseline. Regarding Intubation In Group A maximum number of participants were having good score (56%) followed by poor (30%) and excellent (14%) whereas in Group B excellent score was maximum (62%) followed by good (32%) and poor (6%). With respect to Train of four stimulation Group B showed decreased response to neuromuscular stimulation from 3 minutes onwards compared to Group A. Bispectral index monitoring, in both groups, showed a decreasing trend at every time interval. Conclusion: Cisatracurium is a potent non-depolarising neuromuscular blocking agent and tracheal intubation can be accomplished with good to excellent intubating conditions according to Steyn’s Modification of Helbo-Hansen Scoring System at 3 minutes following 0.15 mg/kg and 0.2 mg/kg of Cisatracurium. From the study of 100 patients in 2 groups, we found that Cisatracurium in a dose of 3ED95 (0.15mg/kg) has haemodynamic stability in view of Heart rate and Blood Pressure. Cisatracurium at a dose of 0.2mg/kg was more haemodynamically stable than Cisatracurium at 0.15 mg/kg during intubation.